Incipient insular differentiation of Carex firmula (Cyperaceae, former genus Uncinia) in the Juan Fernández archipelago (Chile) - Ridley, Rhonda; Jimenez-Mejias, Pedro (Phytotaxa, 2022)
A morphological and molecular study was carried out on two species of Carex from the former genus Uncinia from mainland South America and Juan Fernández Islands: C. firmula (Kük) J.R. Starr and C. subsacculata (G.A.Wheeler & Goetgh.) J.R.Starr. Both species share the particular character of having articulated pistillate scales that leave behind on the spike rachis a saccate stipe-like appendage after falling. We detected within C. firmula morphological differences between mainland South American specimens and Juan Fernández specimens, mainly regarding flower density and utricle size. On the contrary, the molecular analysis showed no molecular differentiation between the two groups of populations. Whereas, strong molecular and morphological support were found for C. subsacculata. As such, we recommend that the populations of C. firmula found on Juan Fernández and those found in the mainland should be recognised as different subspecies: island Carex firmula subsp. firmula and mainland C. firmula subsp. tenuis (Poepp. ex Kunth) R.Ridley & Jim.-Mejías. We discuss that the morphological differences may be a result of isolation in an oceanic island environment and have effect on seed dispersal. Taxonomic descriptions, images of diagnostic characters and a key are included.